Functionalization of carbon black for Ru complexation towards the oxidative cleavage of oleic acid - Gámez, Sebastián; Magerat, Alixandre; de la Torre, Ernesto; Gaigneaux, Eric M. (Molecular catalysis, 2023)
•Heterogenization of ru through polydopamine and bipyridine on carbon black.•Functionalized carbon Ru-catalysts active in the oxidative cleavage of oleic acid.•Total conversion and 95% of yields after 7 h of stirring at room temperature.•High catalytic activity of carbon black-polydopamine-Ru up to 5 recycling tests. Macroporous oxidized carbon black (CBO) have been functionalized with 4,4′-diamino-2,2′-bipyridine (NH2-bpy) and polydopamine (PDA) allowing the complexation of Ru for the catalytic valorization of oleic acid through its oxidative cleavage. This reaction produces azelaic and pelargonic acids which are highly demanded in pharmacology. Conventional bpy is a well-known chelating agent for Ru and the aim of this work is directed to assess its suitability along with polydopamine in building a stable catalyst in the oxidative cleavage reaction. NH2-bpy was covalently bonded to COOH groups on CBO surface by amidation through an acylation and cross-linking(NHS/EDC). On its side, dopamine was self-polymerized in contact with CBO. The success of the deposition of NH2-bpy and PDA was confirmed by FTIR, TGA, and N2 physisorption, while Ru complexation was determined by ICP and XPS analyses. Among the three catalysts, the catalyst based on PDA was the most promising one, reaching a complete conversion of oleic acid with yields of pelargonic and azelaic acids around 95%. Although hot-filtration tests confirmed the presence of Ru species in the reaction medium, the PDA catalyst remained active even after five runs. Actually, post-catalysis characterization of the solid revealed that catechol groups of PDA re-adsorb Ru species once the reaction ends thereby ensuring the reusability of the heterogeneous catalyst. [Display omitted]